2010
DOI: 10.1021/ac101629x
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Confocal, Multichannel Parallel Scan Hyperspectral Fluorescence Imaging Method Optimized for Analysis of Multicolor Microarrays

Abstract: The microarray technique, which can provide parallel detection with high throughput in biomedical research, has generated considerable interest since the end of the 20th century. A number of instruments have been reported for microarray detection. In this paper, we have developed a quasi-confocal, multichannel parallel scan hyperspectral fluorescence imaging system for multicolor microarray research. Hyperspectral imaging records the entire emission spectrum for every voxel within the imaged area in contrast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The width of the entrance slit is 12 μm, which is set in accordance to the width of the focused line light. This spectrometer offers a high spectral resolution of 0.2 nm [9], which is good in separating spectra in most multicolor assays. A CCD array (Canon 500D) is used to capture the spectrally resolved images, and a personal computer carries out further data analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The width of the entrance slit is 12 μm, which is set in accordance to the width of the focused line light. This spectrometer offers a high spectral resolution of 0.2 nm [9], which is good in separating spectra in most multicolor assays. A CCD array (Canon 500D) is used to capture the spectrally resolved images, and a personal computer carries out further data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the contamination induced by fabrication chemistry as well as the emissions from the substrates [7] may affect the determination of gene or protein expressions [8]. To overcome these problems, we have previously developed a quasi-confocal, parallel scan hyperspectral fluorescence imaging system, which has been successfully applied to microarray analysis [9]. The hyperspectral fluorescence approach works by recording full spectra of all the points on the sample plane via a spectrometer [810].…”
Section: Introductionmentioning
confidence: 99%
“…To detect multiple mutations, melting curves of multiple samples are analyzed by using similar analyzers to those used for qPCR. 6,7 As for nucleic-acid-hybridization-based analysis on a microarray plate 8,9 or a microtiter plate, 10 multi-ple target DNA or RNA fragments are immobilized and independently detected. As for an antigen-antibody-reaction-based immunoassay on a microarray plate 11,12 or a microtiter plate, 13 multiple target proteins are immobilized and independently detected.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has developed this technology by using the method of quasi-confocal and multichannel parallel scanning to analyse multicolor microarrays. The advanced method has exhibited great potential for applications in microarrays [22]. In our previous work [23], we proposed SPR-supporting sensing structures based on symmetrical CPWR and the experimental results showed that the sensing characteristics of this symmetrical CPWR based sensor are greatly improved over conventional SPR sensors (a refractive index resolution of 8.1 × 10 −8 RIU and 3.5 × 10 −7 RIU in water and line on the sensor films to cover all the channels of the microfluidic system for fluorescence excitation, and thus multiple channels can be monitored simultaneously at a dark field.…”
Section: Introductionmentioning
confidence: 99%